Challenges in education and training to develop Malaysian construction workforce - Hassan, Padzil Fadzil; Mat Noor, Mohd Sallehuddin; Mohammad, Hairuddin (Universiti Tun Hussein Onn Malaysia, 2021)
Education and training have been central to the development of the Malaysian construction workforce. Notwithstanding the various initiatives introduced to promote education and training, critics are arguing that these have been ineffective. This paper critically reviews the phenomenon and identifies the causal factors. Throughout three key areas; (i) the context of the industry, (ii) the education and training provisions offered, and (iii) the challenges, meta-data analysis of literature was undertaken grounded on the concepts of strategic management ecosystems. Since it is crucial to ties several variable clusters in order to reach a comprehensive finding, the analysis was helped by the multi-layered thematic processes. The findings show that nine key factors at the construction industry level (external ecosystem), and two key factors in the education and training provisions (internal ecosystem) that are interrelated to each other have significantly affected the effectiveness of the education and training to develop the Malaysian construction workforce. These factors need to be addressed in a holistic and integrated manner to improve the predicament which resides in a public strategic management field. Aside from the context-centric findings, the paper posits for subsequent empirical exploration as validation is of concerned. However, it may open up education and training literature to recognised possible multidisciplinary research, education, and practice while addressing challenges such as law, government policy, and standards‟ development.